Performance evaluation of ad hoc on-demand distance vector routing protocol under video streaming - Ahmed, Diaa Eldin Mustafa; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Yagoub, Mudathir (IEEE, 2018)
Video streaming becomes an essential requirements in everyday life. It has been received a great attention from industry and researchers for better human life. To achieve of users demands, an efficient networks protocols should be used. The most popular networks is Mobile Ad hoc Networks. It is a form of movable non-wire networks that a self-configured and self-organized network. The routings are the core of component that sends data from sources to destinations though wireless nodes. This paper investigates the performance of Ad hoc On-Demand Distance Vector (AODV) Routing Protocol under video traffic over PHY IEEE 802.11g. A different scenarios of video streaming were used. The metric in terms of throughput, end to end delay, packet delivery ratio and routing overhead were measured.